FORMULAIC STRUCTURE IN THROUGH THE LOOKING GLASS BY LEWIS CARROLL - Zafirna Arrofifah; Hat Pujiati; Irana Astutiningsih (Haluan Sastra Budaya, 2021)
This article focuses on the formulaic stucture in a popular children’s literature entitled “Through the Looking Glass” by Lewis Carroll. This is aimed to analyze the formulaic stucture of the novel and the elements that caused the novel to become a popular children’s literature in Victorian era, which is undoubtedly related to the Victorian values in Britain.Formula theory by John G. Cawelti is used to analyze the novel. The story of the novel is about a little girl named Alice who wants to be the queen when she is stranded in another world called Looking Glass after leaning into a mirror in her painting room. Result of this research shows that Lewis Carroll’s “Through the Looking Glass” is written using adventure typologyshown through a hero with a goal to reach. The novel also uses fantasy and Victorian era setting to support the suspense.Furthermore, what made the story popular in the era is the need of escape provided by the novel for Victorian children through Alice’s adventure.